School Counsellors’ Perceptions of their Effectiveness - Gora, Rhonda; Sawatzky, Donald; Hague, William (Canadian Journal of Counselling and Psychotherapy, 2009)
This exploratory study investigated the perceptions of school counsellors regarding their effectiveness. The sample consisted of the entire population of counsellors within an urban school district, and included 30 school-based resident counsellors and 8 staff specialists. Participants were interviewed utilizing the Critical Incident Technique. Analysis of the interviews resulted in the identification of eight problem area in which counsellors perceived havingan impact or in which there was little perceived impact. The participants also identified a number of variables that were instrumental in their effectiveness. Counsellors pointed to several barriers that prevented them from meeting the needs of students, including high student-to-counsellor ratios, increasing numbers of crisis cases, and inadequate training to handle certain problems. This study points out the possibilities of counsellors, administrators, and counsellor educators working to improve the effectiveness of school counselling services.